Technology Integration And Student Engagement In Teaching And Learning Contexts - Nur 'azah (Journal of Teaching and Learning, 2026)
This article examines how technology integration influences student engagement in teaching and learning contexts. The study addresses three dimensions of engagement, namely behavioral, emotional, and cognitive engagement, in order to understand how digital tools shape students’ participation, feelings, and mental investment in learning. A qualitative design using library research was employed. Relevant journal articles, books, and academic publications on educational technology, digital learning, and student engagement were identified, selected, and analyzed through a thematic interpretive process. The findings show that technology integration strengthens behavioral engagement through interactive participation, flexible access, and continuous involvement in learning tasks. It also supports emotional engagement by increasing interest, confidence, enjoyment, and a sense of belonging through dynamic and inclusive learning experiences. Cognitive engagement is enhanced through inquiry-based activities, self-paced learning, reflective processes, and collaborative knowledge construction. The study concludes that technology becomes educationally meaningful when it is aligned with learning objectives, supported by purposeful instructional design, and used to create active, inclusive, and intellectually rich learning environments for students.